LATEST INFORMATION WEB APPLICATIONS USING TRIAD THE PROGRAMMING LANGUAGE PHP AND MACROMEDIA DREAMWEAVER - Tino Qomariyadi; Rahayu Noveandini SKom., MMSI Rahayu Noveandini SKom., MMSI (Jurnal Sistem Informasi, 2005)
Making a web application is the latest information using library research methods.The goal is to make it easier for people to get the most recent information. Thisapplication is very useful especially an age now where people that need the ease andspeed in obtaining the latest information.